The innocent's story - Singer, Nicky 1956- (Oxford University Press, 2005)
Thirteen-year-old Cassina Dixon narrates her existence after being killed in a terrorist bombing, when, as a "para-spirit," she passes through a series of hosts, including the bomber and the religious zealot who would force him to kill again